Geochemical Characterization of Irati And Palermo Formations (Paraná Basin–Southern Brazil) for Shale Oil/Gas Exploration - da S. Ramos, Alessandro; Rodrigues, Luiz F.; de Araujo, Gabriel E.; Pozocco, Caroline T. M.; Ketzer, João M. M.; Heemann, Roberto; Lourega, Rogerio V. (Energy technology (Weinheim, Germany), 2015)
Shale gas/oil currently are two of the most important unconventional energy resources. Their exploitation has caused an energy revolution in USA, and many countries are investing in it. Brazil has large areas covered with sedimentary basins, but little attention has been devoted to the study of shale containing oil and gas. The parameters analyzed and studied for geochemical data evaluation are: clay mineral identification, mineral matter analysis, elemental analysis (including total organic carbon, total carbon, H, N, and S), and the methane adsorption capacity of shale. Adsorption in Palermo Formation samples (depth 238.5 m) was 13.72 cm3 g−1 and for samples from Irati Formation (depth 218.45, 95.3, and 107.5 m) 11.73, 6.17, and 4.61 cm3 g−1. Brazilian shale: Shale gas and oil represent important unconventional energy resources. As this new technology is an important subject in chemical engineering, experiments using Brazilian shale have been performed. The parameters analyzed and studied for geochemical data evaluation are: clay mineral identification, mineral matter analysis, elemental analysis (including total organic carbon, total carbon, H, N, S), and the methane adsorption capacity of shale.